Peningkatan Hasil Belajar Matematika Melalui Model Problem Based Learning Pada Siswa Kelas II SDN Kalicari 01 - Sholihatuzzahroh, Nofia (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This research aims to analyze the improvement in student learning outcomes in Matematika learning using the Problem Based Learning model. This class research was carried out in class II of SDN Kalicari 01, totaling 27 students, which lasted for 2 cycles. Each cycle consists of two meetings. The dependent variable is student learning outcomes and the independent variable is the Problem Based Learning model. Data collection methods used include interviews, observation, tests and documentation with quantitative and qualitative analysis techniques. The research results showed that student learning outcomes after applying the Problem Based Learning model in Cycle I obtained a score of 73 and student completion reached 78%. The increase in learning outcomes in cycle II was 81 and the percentage of student completion was 89%. So the application of the Problem Based Learning learning model can improve the Mathematics learning outcomes of class II students at SDN Kalicari 01.